Colour in theory and practice - Seiferlein, Werner; Kötter, Rudolf; Trautwein, Katrin (The Networked Health-Relevant Factors for Office Buildings, 2020)
As we have seen, colour is the interaction between light and surface. n, which makes the world visible to us thanks to our constant absorption of light energy. The colouring of our surroundings is physiologically and psychologically of great importance-the atmosphere shape en, movement and more only become visible through colour differences. Thus the colour pigments absorb some of the light in the room and create the atmosphere with the remaining one. The frequency and intensity of the colour contrasts direct our attention to what seems unconsciously important to us. Our emotional reactions are linked to spontaneous visual experiences (cf. Cuykendall and Hoffman in From Color to Emotion. Ideas and Explorations. University of Irvine Press, Irvine, CA, 2008), whereby aggressive colour landscapes claim our perception more than harmonic ones. They are tiring in the long run because they are too rich in contrast, poor in contrast or too colourful and deviate from our experience of nature, which is characterized by soft colour effects. The colours of nature change constantly in the course of daylight and thus appear lively. Bringing a natural atmospheric effect into the room is the noblest task of the colour designer. Good colour concepts are skilfully designed colour landscapes that are adapted to the light, physiologically non-tiring and psychologically stimulating. Materially and conceptually, they refer to the colours and colour images of nature that have shaped us evolutionarily (cf. Lamb in Eye, 30:179-185, 2016; Cuykendall and Hoffman in From Color to Emotion. Ideas and Explorations. University of Irvine Press, Irvine, CA, 2008). The material implementation of the colour concept takes place with natural colour nuances and even more with natural colours and materials. The use of artificially pigmented colours is an optical deception manoeuvre that imposes a visual dissonance on people in space and suppresses the feeling of being close to nature. Good colour concepts offer convincing answers to three questions. First, how is the atmosphere? The choice of the light main colour is of fundamental importance. Second, what's important in this room? Views are led to light, contrasts of light and dark structure the architecture. Three, am I comfortable here? Dynamic colour accents set with empathy give people the feeling that they are not arbitrary and interchangeable. The checklist in Sect. 10.1 summarizes the most important practical considerations that lead to a good choice of colours. For practical instructions and further information on the design approach described here, reference can be made to specialist seminars which deepen the subject (cf. Trautwein in Colour concepts with light and shadow colours. Seminar contents and dates at www.ktcolor.ch. Uster, Switzerland, 2017).
CRIS-Team Scopus Importer:2024-12-16